Alimentación y compentencia entre Opeia obscura (Thomas) y Paropomala virgata (Scudder); (Orthopetera: Acrididae), en un pastizal de Hilaria mutica del Bolsón de Mapimí, Dgo., México - Rivera García, Eduardo (Instituto de Ecología, A.C., 1990)
Food relationships between Opeia obscura (Thomas) and Paropomala virgata (Scudder) on a tobosa grassland (Hilaria mutica), were studied, species food composition was determined by microhistological analysis of gut contents; niche breadth, food preferences, and food resource utilization were determined for both species and food competence between sexes in both species for host plant composition: females have a wider niche breadth than the males. O. obscura made use of the available food resources better than P. virgata in the tobosa grassland, in the Mapimi Biosphere Reserve, Durango, México; food competence between species was high, the competition is higher in females; males of both species showed differences (P>0.01) on host plant composition.